1997
DOI: 10.1053/gast.1997.v112.pm9041255
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-induced apoptosis during the poisoning of mice with hepatotoxins

Abstract: Hepatotoxins such as alpha-amanitin may induce liver failure by an indirect mechanism involving sensitization of parenchymal cells toward endogenously produced TNF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
128
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(133 citation statements)
references
References 61 publications
2
128
0
3
Order By: Relevance
“…It is well characterized that NRF2 stimulates the antioxidant defense system in response to oxidative stress, and it could be speculated that the decreased expression of NRF2 by α-AMA may be involved in the cytotoxicity of α-AMA (36). Furthermore, tumor necrosis factoralpha aggravates the α-AMA cytotoxicity by a mechanism that may involve reactive oxygen species (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…It is well characterized that NRF2 stimulates the antioxidant defense system in response to oxidative stress, and it could be speculated that the decreased expression of NRF2 by α-AMA may be involved in the cytotoxicity of α-AMA (36). Furthermore, tumor necrosis factoralpha aggravates the α-AMA cytotoxicity by a mechanism that may involve reactive oxygen species (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in several pathological conditions (e.g. brain ischemia; Linnik et al, 1995;Beilharz et al, 1995;Portera-Cailliau et al, 1995;Charriaut-Marlangue et al, 1996), liver damage by cytokines or toxins (Leist et al, 1995(Leist et al, , 1997b) demise can occur simultaneously by necrosis or apoptosis. Work in our laboratory and in collaboration with Dr SA Lipton and Dr S Orrenius has previously shown that the intensity of the same initial insult decides the prevalence of either apoptosis or necrosis (Dypbukt et al, 1994;Bonfoco et al, 1995).…”
Section: Energy Supply and Cell Death P Nicotera And M Leistmentioning
confidence: 99%
“…In actinomycin D-primed C3H/HeJ mice treated intraperitoneally with SEB, liver injury was initially characterized by mild congestion, accumulation of polymorphonuclear leukocytes in sinusoids, and later by focal necrosis of hepatocytes (9). Actinomycin D itself also caused apoptosis of hepatocytes (19). Our intranasal SEB-induced murine toxic shock model showed that SEB itself could provoke liver congestion, apoptosis of hepatocytes, and portal inflammation.…”
Section: Morbidity and Mortalitymentioning
confidence: 72%